AN ANALYSIS OF ENGLISH REGISTER USED ON MAKEUP TUTORIAL CONTENTS IN INDIRA KALISTHA YOUTUBE CHANNEL - Almira Rahma Syastuti; Rahmaditya Khadifa Abdul Rozzaq Wijaya (Universitas Duta Bangsa Surakarta, 2024)
Register is a variety of language that used to communicate in certain group. In Sociolinguistics, register is a term in the specific lexical and grammatical selection used by speakres depending on the context and situation. This research focused on the types and the function of register used on makeup tutorial contents in Indira Kalistha YouTube Channel. This research used descriptive qualitative research design, which describe the register phenomena used in makeup tutorial contents. The data were analyzing by identifying word and phrase. Based on findings and siscussion data, the total data found in this study were 35 data examined and categorized into 24 words and 11 phrases.